2019
DOI: 10.1103/physrevc.99.054331
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear level densities and γ -ray strength functions in samarium isotopes

Abstract: The γ-strength functions and level densities in the quasi-continuum of 147,149 Sm isotopes have been extracted from particle-γ coincidences using the Oslo method. The nuclei of interest were populated via (p,d) reactions on pure 148,150 Sm targets and the reaction products were recorded by the Hyperion array. An upbend in the low-energy region of the γSF has been observed. The systematic analysis of the γSF for a range of Sm isotopes highlights the interplay between scissors mode and the upbend. Shell-model ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…It was found that the low-energy M 1 strength decreases and the scissors strength develops when going into the open shell. The simultaneous appearance of the two M 1 modes is in accordance with experimental findings in Sm isotopes [6,7]. Later on, M 1 strength functions were calculated for isotopic series in various mass regions [16][17][18].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was found that the low-energy M 1 strength decreases and the scissors strength develops when going into the open shell. The simultaneous appearance of the two M 1 modes is in accordance with experimental findings in Sm isotopes [6,7]. Later on, M 1 strength functions were calculated for isotopic series in various mass regions [16][17][18].…”
Section: Introductionsupporting
confidence: 83%
“…First observed in 56,57 Fe [3], the upbend was found also in various nuclides in other mass regions, such as in Mo isotopes [4], in 105,106 Cd [5], and in Sm isotopes [6,7]. The experiments used light-ion induced reactions such as ( 3 He, 3 He'), and the data were analyzed with the so-called Oslo method to extract level densities and γ-SFs.…”
Section: Introductionmentioning
confidence: 99%
“…[11] concluded that the bimodal structure gradually develops with increasing N by shifting strength from the LEMAR spike to the SR while the sum stays nearly constant. The gradual development of the SR and the shift of the integrated strength when entering a shell has been confirmed experimentally for odd-A Sm isotopes [18]. Systematic calculations using the full pf shell as configuration space for the Ge isotopes [19] and the Ga isotopes [9] show that near the closed shells N = 28 and 50 only the LEMAR spike exists.…”
Section: Deformationmentioning
confidence: 88%
“…In the shell-model calculations, such a bump appears in open-shell nuclei and has been related to the scissors resonance, which develops in deformed nuclides [75]. A pronounced bump around 3 MeV in addition to the low-energy upbend was also observed in Sm isotopes [76,77].…”
Section: Discussionmentioning
confidence: 99%

Photoexcitation of $^{76}$Ge

Schwengner,
Massarczyk,
Schmidt
et al. 2021
Preprint
Self Cite